Side effects of a forest carbon rent policy on soil GHG emissions and nutrient export from forests - Rautiainen, Aapo; Pohjola, Johanna; Assmuth, Aino; Lintunen, Jussi (Oxford University Press, 2026)
Member states of the European Union (EU) have targets to increase net CO2 removals in the Land Use, Land Use Change and Forestry sector. As Finland threatens to fall short of its target, measures to strengthen its forest CO2 sink have been called for. One option would be to implement a carbon rent policy to incentivize increased carbon storage in standing timber and wood products. However, such a policy might have unintended side effects on nutrient loads in runoff from forests, and soil GHG emissions from forests on peatlands. Here, we assess these side effects using FinFEP, a dynamic partial-equilibrium model of the Finnish forest and energy sectors. Our results suggest that a carbon rent policy could be expected to decrease nitrogen (N) and phosphorus (P) loads in the short run, but not in the long run. Net GHG emissions from the decomposition of peat could be expected to increase, but the increase would be small compared to the policy’s overall effect on the forest CO2 sink. Hence, neither of these examined side effects appears to provide a reason to reject the policy.
Keywords: nutrient export; carbon rent; climate policy; LULUCF; boreal forest; organic soil; GHG emissions